Avoiding pitfalls, conquering fears. (February 2012) - Singh, Digvijay; Saxena, Rohit
The Delhi Ophthalmology Society Mid-Term Conference 2011 was a pan-ophthalmology meet. Scientific symposia and academic lectures covering all subspecialties focused on the theme of 'Avoiding pitfalls conquering fears''. This report covers the prominent aspects of this meeting including the live specialty surgery session, glaucoma session, squint and neuro-ophthalmology symposium and pediatric ophthalmology symposium.